STUDI EMPIRIS PADA KINERJA ORGANISASI : Budaya Organisasi Sebagai Variabel Moderasi - Muhammad Heno Rifdas Hafizh (2020)
Purpose- This study is based on IHPS BPK RI 2017 in the second semester. There are problems in terms of the performance of local governments in Lampung Province. The purpose of this study is to analyze the effect of 4 successful factors of AIS consisting: service quality, information quality, data quality, and system quality on organizational performance moderated by organizational culture. Methodology- The population of this study is 29 Regional Apparatus Organizations (RAO) in South Lampung Regency using a saturated sample. Contingency theory is the basis of this study in order to form a mindset connecting four successful factors of AIS supported by the organizational culture of the leadership of the RAO on organizational performance. The analysis technique uses Structural Equation Model (SEM) through the SMART PLS version 3.0 application. Findings- The results of this study indicate that there is a significant positive impact on organizational performance which has been presented by service quality. On the other hand, organizational performance is not influenced by information quality, data quality, and system quality. Whereas, the organizational culture does not constrain the relationship of service quality, information quality, data quality, and system quality on organizational performance. Conclusion- This study concluded that service quality is positve significantly on the organizational performance. Whereas, the information quality, data quality, and system quality insignificant relationship with the organizational performance in regional apparatus organizations. Therefore, further studies could be conducted to include other variables such as employee motivation, employee performance, self-efficacy, in indonesian local government.